Human-in-the-Loop Simulations Methods and Practice - Rothrock, Ling.; Narayanan, S.; SpringerLink (Online service) (London : Springer London, 2011)
Human-in-the-Loop Simulations is a compilation of articles from experts in the design, development, and use of human-in-the-loop simulations. The first section of the handbook consists of papers on fundamental concepts in human-in-the-loop simulations, such as object-oriented simulation development, interface design and development, and performance measurement. The second section includes papers from researchers who utilized HITL simulations to inform models of cognitive processes to include decision making and metacognition. The last section describes human-in-the-loop processes for complex simulation models in trade space exploration and epidemiological analyses. Human-in-the-Loop Simulations is a useful tool for multiple audiences, including graduate students and researchers in engineering and computer science.
1. Interactive Simulations: History, Features, and Trends -- 2. Performance Measurement and Evaluation in Human-in-the-Loop Simulations -- 3. Virtual and Constructive Simulations with the GRBIL Modeling Tool -- 4. An Integrated Pedestrian Behavior Model Based on Extended Decision Field Theory and Social Force Model -- 5. Determining the Number of Simulation Runs: Treating Simulations as Theories by Not Sampling Their Behavior -- 6. Training for Metacognition in Simulated Environments -- 7. Trade Space Exploration: Assessing the Benefits of Putting Designers "Back-in-the-Loop" During Engineering Optimization -- 8. Analyzing Global Epidemiology of Diseases Using Human-in-the-Loop Bio-Simulations -- 9. Aiding Understanding of a Contested Information Environment's Effect on Operations -- 10. Interactive Model-Based Decision Making for Time-Critical Vehicle Routing -- 11. PerFECT: An Automated Framework for Training on the Fly -- 12. Evaluating Human Interaction with Automation in a Complex UCAV Control Station Simulation Using Multiple Performance Metrics.
Keywords: COMPUTER SCIENCE; COMPUTER SIMULATION; PHYSICS; ENGINEERING; COMPUTER SCIENCE; SIMULATION AND MODELING; USER INTERFACES AND HUMAN COMPUTER INTERACTION; COMPLEXITY